Évaluation de l’activité antifongique et de la phytotoxicité de Isoberlinia doka craib & staff - Ouédraogo, Harouna; Ouattara, Lassina; Ouoba, Paulin; Bonzi, Schémaeza; Somda, Irénée (European Scientific Journal, ESJ, 2018)
This study has been designed to contribute to search alternative solutions based on plant extracts against phytopatogenic fungi. It aims to test the efficacy of ethanolic extract (70%) of Isoberlinia doka trunk bark on the mycelial growth of eight phytopagenic fungi species and on maize and cowpea seedlings germination and growth. The results showed that the ethanolic extract inhibits mycelial growth. This extract has showed an interesting efficiency on three fungi such as Colletotrichum dematium, Curvularia lunata and Fusarium verticilloides. Among these fungi, Curvularia lunata was the most sensitive with a rate of inhibition of mycelial growth of 52.35% after four days incubation at 10 mg / ml. After seven days incubation, the extract was more effective in reducing Fusarium verticilloides mycelial growth with 50,70% inhibition rate at the same concentration. After the phytotoxicity tests, it was found that this extract had no phytotoxic effect on the germination and growth of maize seedlings while it reduced significantly seed germination and cowpea seedling growth. The ethanolic extract of I. doka bark has antifungal properties and did not inhibited maize growth parameters. It could be used in maize seed treatment. Investigations could also be made into the herbicidal properties of some invasive legumes close to cowpea.